Phenomenological Examination of Spiritual and Religious Coping Styles of Mothers Grieving a Child with Cancer - Sajadipour , Farideh Sadat; Dehghan Manshadi, Marieh; Sedrpushan , Najmeh; Fallah, Mohammad Hosein (Psychology of Woman Journal, 2024)
Objective: The death of a child is arguably the most difficult experience a mother can face, accompanied by numerous psychological traumas. Particularly, the death of a child due to cancer poses unique challenges. Therefore, the way mothers cope with this grief is of great importance to alleviate their distress and psychological damage. Among various coping mechanisms, spiritual and religious coping in grief, especially within a religious culture, holds a special place and significance. Accordingly, the aim of this research was to examine the spiritual and religious coping styles of grieving mothers based on their lived experiences. Methods and Materials: This study was qualitative and phenomenological in nature. Purposeful sampling with maximum variation was employed. The sample consisted of 13 bereaved mothers who had lost a child to cancer in the city of Yazd. Data were collected through semi-structured interviews. Following the interviews, which were recorded, each interview was transcribed and analyzed using Colaizzi’s method. Findings: Ten themes emerged from the data analysis. These themes included resignation to fate, providence, gratitude, recalling the tribulations of the Imams, charity, recitations, divine testing, perspectives on death and the hereafter, prayer, and patience. Conclusion: These findings suggest that spiritual and religious coping styles are significantly utilized by mothers grieving a child with cancer, and these themes could be used for effective interventions to reduce grief symptoms and educate on coping with grief.